Pertimbangan Hakim terhadap Pemufakatan Jahat dalam Tindak Pidana Narkotika Golongan I: Studi Putusan Pengadilan Tinggi Tanjung Karang Nomor 247/Pid.Sus/2024 dalam Perspektif Hukum Islam - Prabowo, Edo Arya; Jainah, Zainab Ompu; Ainita, Okta (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
Criminal conspiracy in narcotics offenses represents a form of organized crime that poses a serious threat to society and the state. This research aims to analyze the criminal liability of the defendant involved in a conspiracy to possess Class I non-plant-based narcotics, as examined in the High Court Decision No. 247/Pid.Sus/2024/PT Tjk. This study uses a normative juridical and empirical juridical approach. The normative juridical method is based on the review of relevant legal sources, particularly Law No. 35 of 2009 on Narcotics. The empirical juridical method includes interviews with law enforcement officers to understand the application of the law in practice. The results show that the defendant was proven legally and convincingly to have engaged in a criminal conspiracy to unlawfully possess Class I narcotics, specifically methamphetamine (sabu). The judge applied Article 112 paragraph (1) in conjunction with Article 132 paragraph (1) of the Narcotics Law, sentencing the defendant to 7 years of imprisonment and a fine of IDR 1,000,000,000 with a subsidiary of 3 months of detention. This ruling reflects an integrated criminal justice process—investigation, prosecution, and sentencing—that prioritizes fairness and legal certainty. This research recommends that law enforcement officials improve professionalism, independence, and consistency in applying conspiracy provisions to enhance deterrence and combat narcotics distribution more effectively.